Acute toxicity of nitrite in fat snook (Centropomus parallelus). Issue 1 (2nd January 2018) - Lima Rodrigues, Andressa de Souza; Gnocchi, Karla Giavarini; Delunardo, Frederico Augusto Cariello; Medeiros, Laila Carine Campos; Merçon, Julia; Gomes, Levy Carvalho
Abstract: Oxidative stress and hypoxia responses in Centropomus parallelus exposed to three different concentrations of nitrite (0, 0.5, and 10 mg L −1 ) were evaluated. To determinate toxicity, we used enzymatic analyses and quantifications of oxygen consumption and opercular beats under conditions of normoxia and hypoxia. There was no significant difference in GST, CAT, or GPx enzymes in the liver or in GPx in the gills. Levels of GST were altered at a concentration of 10 mg L −1 in experiment I. Experiment II displayed alterations for GST and CAT in the liver at the same concentration, indicating that exposure to nitrite does not generate differentiated activation in the body's defense system by the production of oxidative stress enzymes. When nitrite was associated with hypoxia, there was a significant increase in both enzymatic activity and opercular beating under hypoxia in the group exposed to 10 mg L −1 nitrite compared to the control.